Diagnostic Reference Level of Computed Tomography Examinations and Need for Dose Optimization in Ondo State, Nigeria - Oluwakayode Oyedokun; Adeseye Arogunjo; Joseph Fatukasi; Adedeji Egberongbe (Iranian Journal of Medical Physics, 2020)
Introduction: The present study was conducted to obtain State diagnostic reference levels (DRLs) of five routine computed tomography (CT) examinations from two CT centers in Ondo State and to identify factors responsible for dose variation and escalation in these CT centers. Material and Methods: Acquisition parameters and CT dose indices were collected from the storage drives of the two CT centers namely Federal Medical Centre, Owo and Trauma Center, Ondo, Ondo State, Nigeria, for six months on electronic spreadsheets for cranial, sinus, chest, abdomen and pelvis examinations. In addition, dose indices for multiphase examinations were collected to analyze chest and abdominal doses. Wilcoxon rank-sum test was used to assess variations in dose distributions of the two health institutions. Results: The following diagnostic reference levels (DRLs) were obtained at 91 mGy; 1943 mGy.cm, 69 mGy; 1159 mGy.cm, 45 mGy; 1064 mGy.cm, 50 mGy; 2545 mGy.cm and 26 mGy; 622 mGy.cm in cranial, sinus, chest, abdomen and pelvis examinations respectively. Conclusion: Estimated State DRLs exceed national and other DRLs indicating that there is a need to improve the quality of CT-examination for a better benefit to risk ratio.However, benchmarking DRLs to median dose levels (Achievable dose levels) instead of the upper quartile will be a good starting point in achieving the optimal dose level.